2008
DOI: 10.1007/s10608-008-9206-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Development of Perfectionistic Cognitions and Self-Beliefs

Abstract: In a sample of 187 adolescent-parent pairs the relationships between parent behavior and adolescents' self-reported perfectionistic tendencies (i.e., concerns over mistakes, doubts about actions and personal standards) and self-beliefs (i.e., self-esteem, contingent self-worth and labile self-esteem) were explored. Hierarchical regression analyses indicated that adolescents' tendency to doubt their actions was positively predicted by maternal self-reported psychological control and negatively predicted by adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…In addition, we used the three subscales from the Frost Multidimensional Perfectionism Scale (FMPS; Frost et al, 1990) capturing personal standards (seven items; e.g., "I have extremely high goals"), concern over mistakes (nine items; "I should be upset if I make a mistake"), and doubts about actions (four items; "I usually have doubts about the simple everyday things I do"). All scales have demonstrated reliability and validity in numerous studies with adolescents (e.g., Ablard & Parker, 1997;Damian et al, 2014a;Essau, Leung, Conradt, Cheng, & Wong, 2008;Hewitt et al, 2002;McArdle, 2009;Soenens et al, 2008). To obtain the two higher-order dimensions of perfectionism, we followed Dunkley et al (2000), combining (a) self-oriented perfectionism and personal standards to capture perfectionistic strivings and (b) socially prescribed perfectionism, concern over mistakes, and doubts about actions to capture perfectionistic concerns (see also Enns et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we used the three subscales from the Frost Multidimensional Perfectionism Scale (FMPS; Frost et al, 1990) capturing personal standards (seven items; e.g., "I have extremely high goals"), concern over mistakes (nine items; "I should be upset if I make a mistake"), and doubts about actions (four items; "I usually have doubts about the simple everyday things I do"). All scales have demonstrated reliability and validity in numerous studies with adolescents (e.g., Ablard & Parker, 1997;Damian et al, 2014a;Essau, Leung, Conradt, Cheng, & Wong, 2008;Hewitt et al, 2002;McArdle, 2009;Soenens et al, 2008). To obtain the two higher-order dimensions of perfectionism, we followed Dunkley et al (2000), combining (a) self-oriented perfectionism and personal standards to capture perfectionistic strivings and (b) socially prescribed perfectionism, concern over mistakes, and doubts about actions to capture perfectionistic concerns (see also Enns et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on authoritarian parenting and its relation to negative outcomes have implicated psychological control as a significant factor for maladaptive outcomes such as anger and aggressive tendencies (Campbell, 1999;Coie & Dodge, 1988;Eron, Huesmann, & Zelli, 1991;Rubin & Burgess, 2002). Research on the self has also shown that psychologically controlling parenting is related to maladaptive outcomes such as lower authenticity (Robinson, Lopez, & Ramos, 2014) and instability of self-esteem (Kernis, Brown, & Brody, 2000;McArdle, 2009;Wouters, Doumen, Germeijs, Colpin, & Verschueren, 2013).…”
Section: Psychological Controlmentioning
confidence: 99%
“…Given the relationship of psychologically controlling parenting to authenticity (Robinson et al, 2014) and contingent self-worth (Wouters et al, 2013;McArdle, 2009), and the relation of authenticity to contingent self-worth (Vonk & Smit, 2012), it is possible that authenticity serves as a mediator between parental psychological control and contingent self-worth. As parents impose their own standards above the desires and experiences of the child, it is plausible that inauthenticity and the acceptance of parental standards can play a major role in development and maintenance of contingent self-worth.…”
Section: Authenticity and Contingent Self-worthmentioning
confidence: 99%
“…Hill, Hall, Appleton, and Murray (2010) examined self-oriented and socially prescribed perfectionism and levels of validation seeking and growth seeking in 150 young athletes. Hill et al (2010) posited that perfectionistic athletes would be high in validation seeking because trait perfectionism is underscored by high levels of conditional self-worth and low unconditional self-acceptance (DiBartolo, Frost, Chang, LaSota, & Grills, 2004;Flett, Besser, Davis, & Hewitt, 2003;Hill, Hall, Appleton, & Kozub, 2008;Lundh, 2004;McArdle, 2009;Sturman, Flett, Hewitt, & Rudolph, 2009). It should be noted that Hill et al (2010) used a modified version of the Goal Orientation Inventory (GOI; Dykman, 1998) adapted for sports contexts rather than the general measure used in the current study.…”
Section: Perfectionism and Interpersonal Orientationsmentioning
confidence: 99%